Anmeldelser - Dillmar, Anders (Danish Yearbook of Musicology, 2007)
Review of: Kirsten Sass Bak and Svend Nielsen (eds.): Spiritual Folk Singing. Nordic and Baltic Protestant Traditions. Copenhagen: Forlaget Kragen, 2006